HARMONIC ANALYSIS OF TORSIONAL VIBRATION FORCE EXCITATION - Matej URBANSKÝ (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
In our department, we deal with various methods for the continuous tuning of torsional oscillating mechanical systems during their operation, mainly in terms of torsional vibration magnitude. Therefore, in order to carry out necessary experimental research, we need torsional oscillation exciters, which operate on various principles. The objective of this paper is to conduct a harmonic analysis of a torsional oscillation force excitation mechanism, in order to identify the possibilities of its application.